PROFITABILITY PERFORMANCE ANALYSIS: THE EVIDENCE FROM PRIVATE TELECOMMUNICATION FIRMS IN MALAYSIA (Malaysian Management Journal, 2021)
This paper examines the macroeconomic factors influencing the profitability performance of private telecommunication firms in Malaysia. A yearly basis data between 2007 and 2016, which contained a total number of 49 data observations were analyzed using the Random Effects Model to estimate the factors of concern. The sources of these data have been predominantly extracted from DataStream. The variables involved in this investigation were liquidity (LIQ), leverage (LEV), firm size (SIZE), and gross domestic product (GDP). This study has been motivated by the declining profitability performance of private telecommunication firms in Malaysia, which has been attributed to the decreasing return on assets. The findings suggest that leverage has a significant and negative relationship with return on assets, while liquidity has a negative insignificant towards the firms’ profitability. On the other hand, firm size and gross domestic product have a substantial and positive relationship with return on assets. Moreover, the findings seemed to suggest that the bigger the size of a firm, the higher the total assets would be, which in turn, would improve the firm’s profitable performance. In sum, the prerequisite attribute that a telecommunication firm needed to possess in attaining high profitability performance was its strong and high productivity in the management of its total assets.